Pengembangan Media Animasi Menggunakan Adobe Flash Dalam Pembelajaran Analisis Dinamika Litosfer Mata Pelajaran Geografi Kelas Sepuluh - Firrohmah, Ana Styana, M. Amin Sunarhadi, S.Si., M.P (2015)
Teachers should memilikiki ability on him, one of the teachers' pedagogical abilities are able to develop and utilize pembelajaran.Media media has an important function, namely to clarify the presentation of the message, overcome the limitations of spacetime and the power of the senses, makes the students excited about learning. On the other hand many teachers who have not yet developed learning media.The purpose of this study was to determine the criteria for the product development of animation media in learning lithosphere dynamics analysis. To know animsidalam instructional media development dynamics analysis litosfer.Untuk determine the effectiveness of the dynamics of the lithosphere in learning animation.The method used in this research study development. The study was conducted in SMA Negeri 1 Kartasura. The subjects of the research students of grade ten, and the object of research is animated media in learning geography. The method used in collecting data through observation, interviews and documentation. Methods of data analysis is the quantitative descriptive analysis techniques.Based on the analysis of the results and discussion can be deduced as follows. Criteria for media development for learning animations Lithosphere Dynamics Analysis as follows: full color animation Media, Media animation that is musical, Media animation sound effects, motion animation varies Media, Media animation that is the motivation, Media animation of long duration. Development of animation media lithosphere dynamics analysis on rock material, explaining the process of the formation of rocks. Start of igneous, Seimens, and metamorphic rocks. Animation effective media for learning Lithosphere Dynamics Analysis